(untitled) (Journal of Economic Research & Business Administration, 2018)
The article examines the problem of analyzing the consequences of the financial and economic crisis in terms of impact on the value of business with the purpose of applying restructuring procedures, taking into account the current legislative framework. The solution to this problem is to solve the scientific task of adapting existing mathematical and instrumental methods of business valuation in the Republic of Kazakhstan. Restructuring is also considered in the process of cost management in the following situations: under normal, systematic development of the company in a favorable macroeconomic environment, such as cost optimization, working capital management, etc .; in the deterioration of performance and the company’s condition under the influence of external factors or internal causes. When identifying negative factors in the planned development of the company and in crisis situations, various measures can be taken: under favorable environmental conditions and market growth, the company pays special attention to optimizing business processes and increasing the cost of business; in worsening macroeconomic factors or inefficient business processes, technology lagging, promotion of competition and loss of market share is necessary to improve its stability, solvency, improve business processes and systems for business recovery. Realization of these goals implies solving the tasks of business management in the context of overcoming the consequences of the crisis through the application of various company management strategies. As a result, companies can build a flexible business management system that can meet the challenges in order to reduce the negative effects of the crisis in the short term and to ensure sustainable development and the growth of their value in the long term.